PENGARUH KONSENTRASI AGAR TERHADAP KARAKTERISTIK FISIKOKIMIA DAN ORGANOLEPTIK SELAI LEMBARAN APEL ANNA DAN ROSELLA - Jaya, David Putra; Suseno, Thomas Indarto Putut; Setijawati, Erni (Widya Mandala Surabaya Catholic University, 2017)
Anna apple and rosella jam is defined as jam which is made from sugar, Anna apple, and rosella. This product has a potential to be developed in slice form. The benefits of Anna apple and rosella jam slice are more practical to prepare, carry, stored, and minimize the risk of food contamination. Anna apple and rosella jam slice has compact texture, glossy and is not sticky on its package. Addition of hydrocolloid like agar is solution to get the desired slice jam characteristics. Use of agar can affect physicochemical and organoleptic Anna apple and rosella jam slice, therefore a research is needed to know the effects of agar’ s concentration. The methodology of this research was a randomized block design (RBD) with one factor, that is the concentration of agar (P), which consists of six levels 0.6% (P1); 0.7% (P2); 0.8% (P3); 0.9% (P4); 1.0% (P5); and 1.1% (P6) of Anna apple rosella pure. Repetition of the experiments were carried out four times. Agar concentration difference affected moisture content, pH, hardness, cohesiveness, adhesiveness, and organoleptic score (firmness). Higher concentration of agar caused a declined on moisture content and syneresis level, on the other hand hardness, adhesiveness, cohesiveness, and pH increased. Anna apple and rosella jam slice color was purplish red (L between 26.6-27.4; a* between 2.5-3.1; b* between 0.2-0.6; C between 2.5- 3.0; dan °h between 5.3-11.0°). Best concentration of agar was 1.0% which had moisture content 39.30%, pH 3.69, hardness score 965.221 g, cohesiveness 0.346, adhesiveness score -554.336 g.s, phenolic content 1183.6163 mg GAE/100 g, with sensory score of taste 4.9847, color 5.4659, and firmness 5.5306 with standard score 1-7.